TEACHERS’ PERCEPTIONS AND READINESS TO ADOPT INNOVATIVE AI-DRIVEN TOOLS FOR CUSTOMIZING RECEPTIVE ENGLISH SKILL INSTRUCTION FOR YOUNGER LEARNERS - Ziyadina Bibissara Sayabekkyzy; Golovchun Aleftina Anatolievna (Interdisciplinary Science Studies, 2025)
This quantitative study investigates primary school English teachers’ perceptions and readiness regarding the integration of innovative Artificial Intelligence (AI)-driven tools for customizing receptive English skill instruction for young learners. Traditional instructional models often struggle to manage the inherent heterogeneity in young student populations, creating a pressing need for scalable personalization solutions like AI. However, the successful adoption of these technologies critically relies on the attitudes and preparedness of classroom practitioners. Utilizing a cross-sectional survey design, data will be collected from a convenience sample of primary English teachers using a standardized questionnaire employing a 5-point Likert scale. The instrument assesses teacher perceptions of AI’s potential utility (e.g., diagnostic accuracy, planning time reduction) and identifies key barriers to adoption (e.g., training, funding, data privacy concerns). The findings of this research are expected to contribute valuable insights to the academic literature on educational technology adoption, providing direct feedback for AI developers.